2005
DOI: 10.1002/jcb.20574
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 induces cell death, calpain activation, and MDMX degradation in a transcription independent manner implicating a novel role for E2F1 in neuronal loss in SIV encephalitis

Abstract: The E2F1 transcription factor can initiate proliferation or apoptosis, the latter by both transcription-dependent and -independent mechanisms. Recently, an E2F1 mutant lacking the DNA binding domain, E2F1(180-437), has been implicated in degradation of MDMX and MDM2 proteins via lysosomal proteases. MDM proteins block p53 dependent apoptosis by directly inhibiting p53 stability and function. Here we demonstrate E2F1(180-437) induces death in HEK293 cells independent of E2F1 transcriptional activation and p53 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…L. Jordan-Sciutto et al, 2000). We have also observed decreased expression of a negative regulator of E2F1, murine double minute x/4 (MDMx), in the SIVE brain (Strachan, Koike, Siman, Hall, & Jordan-Sciutto, 2005). …”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…L. Jordan-Sciutto et al, 2000). We have also observed decreased expression of a negative regulator of E2F1, murine double minute x/4 (MDMx), in the SIVE brain (Strachan, Koike, Siman, Hall, & Jordan-Sciutto, 2005). …”
Section: Introductionmentioning
confidence: 82%
“…We previously demonstrated decreased MDMx expression and increased cytoplasmic E2F1 expression in the frontal cortex, basal ganglia and hippocampus of SIV-infected macaques with encephalitis (SIVE), and increased cytoplasmic E2F1 expression in HIVE (Strachan et al, 2005). We further showed that cytoplasmic E2F1 in HEK293 cells is associated with calpain activation and transcription-independent degradation of MDMx (Strachan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the mechanism involved in the regulation of calpain activity leading to apoptosis or necrosis. (70). The main conclusion of this study is that overexpression of calpastatin offers partial neuroprotection against excitotoxicity, and, therefore, modulation of the balance between calpains and calpastatin activities offers a potential therapeutic target for the treatment of neurodegenerative pathologies.…”
Section: Role Of Calpain Activation In Neuronal Cell Deathmentioning
confidence: 92%
“…MEF-2 is localized in the nuclei and promotes neuronal cell death (19,24,67). Still another strategy for the development of new drugs to treat AD could be the overexpression of calpastatin, which might prevent tau phosphorylation (70). The downregulation of calpain activity should attenuate degradation as well as phosphorylation of tau.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…However, studies have shown that neurons express cell cycle molecules from different phases simultaneously or localized in the ''wrong'' subcellular compartment (Copani et al 2001;Ogawa et al 2003;Strachan et al 2005;Qu et al 2007), and it is hypothesized that this aberrant cell cycle could facilitate PCD.…”
Section: Dna Damage And/or Aberrant Cell Cyclementioning
confidence: 98%